1989
DOI: 10.1128/iai.57.1.278-282.1989
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein protects against preerythrocytic stages of malaria

Abstract: We previously reported that low doses of interleukin-1 strongly inhibited in vitro development of the hepatic stages of Plasmodiumfalciparum and P. yoelii. Among several hypotheses, we considered the role of C-reactive protein (CRP), a major acute-phase reactant whose concentration increases markedly in infectious disorders. We demonstrated that human hepatocytes cultured in the presence of interleukin-1 released, as early as 30 min after stimulation, an increased amount of CRP. We then established that CRP bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Both antibodies were a gift from Yupin Charoenvit (Malaria Program, Naval Medical Research Program). Percent parasite inhibition was calculated by comparing the number of schizonts in the experimental cultures with that in controls (= 0% inhibition) (10,11,18,19,(21)(22)(23)(24).…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…Both antibodies were a gift from Yupin Charoenvit (Malaria Program, Naval Medical Research Program). Percent parasite inhibition was calculated by comparing the number of schizonts in the experimental cultures with that in controls (= 0% inhibition) (10,11,18,19,(21)(22)(23)(24).…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…Analysis of the time-course indicated that IL-I did not affect maturation of the parasite or the sporozoite itself, but probably had an indirect effect on the very early phase of infection [43]. One of the first hypotheses we proposed to explain IL-1 activity was the secretion of a non specific factor, the C-reactive protein [51]. Results will be given below.…”
Section: Effects Of Cytokinesmentioning
confidence: 99%
“…Participation of such nonspecific factors, e.g. acute-phase proteins, has been postulated to explain the mode of action of IL-I [43,51]. Acute-phase proteins, and particularly the C-reactive protein (CRP), are synthesized at a higher rate when hepatocytes are stimulated with IL-1 [32, 5 I, 52].…”
Section: Nonspecific Factorsmentioning
confidence: 99%
“…CRP, also referred as acute phase protein, has binding sites for diverse ligands that contribute to multifunctional properties of the protein. The levels of CRP are enhanced during infection (10), and in many parasitic infections such as the pre‐erythrocytic stages of Plasmodium yoelli (11), Schistosomiasis (12) and Hymenolepes diminuta (13), the elevated CRP was found to be protective. Adult H. diminuta when incubated in CRP containing serum lost motility and showed damaged tegument similar to parasite damage resulting from an immune attack or complement‐mediated lysis.…”
mentioning
confidence: 99%